Regulación del español en la inteligencia artificial: un nuevo giro en la discursividad panhispánica - Iglesias Sánchez, Agostina Belén (2025)
The public sphere of language is affected by the current global and technocratic scenario that permeates its strategic agenda. The Royal Spanish Academy plays a leading role in the standardization of language in digital spaces and in artificial intelligence technologies. Through the Lengua Española e Inteligencia Artificial project, the institution is promoting the consolidation of Spanish as an international language. This standardization and simplification of the language put an end to the panhispanic discourse and inaugurated a “new era” in the Academy's work. From a glottopolitical perspective, this paper proposes to examine how this discursive turn is constructed and the normative model(s) it postulates, taking into account the linguistic varieties that the policy prioritizes, and the extra-linguistic demands to which it responds.